Gastrointestinal stromal tumors with the use of ripretinib and sunitinib: real-world adverse event analysis based on the FDA adverse event reporting system (FAERS) - Che, Xinzhen; Zhu, Yong (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to analyze potential adverse events (AEs) associated with ripretinib and sunitinb in gastrointestinal stromal tumor (GIST) treatment using data from the FDA Adverse Event Reporting System (FAERS). The findings provide insights for future research to improve the safety and clinical management of ripretinib and sunitinib.MethodsAdverse Drug Event (ADE) reports related to ripretinib and sunitinib were extracted from the FAERS database, covering the period from Q2 2020 to Q4 2024 and Q1 2006 to Q4 2024, respectively. ADEs were classified and described according to Preferred Terms (PTs) and System Organ Classes (SOCs) in the Medical Dictionary for Regulatory Activities (MedDRA). Disproportionality analysis, including Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-Item Gamma Poisson Shrinker (MGPS), was employed to identify significant signals.ResultsA total of 3,636 and 34,768 ADE reports related to ripretinib and sunitinib were identified using four disproportionality analysis methods. The top five ADR signals for ripretinib include hepatic embolization, tumor compression, hyperkeratosis, tumor excision and tumor pain. For sunitinib, the five strongest ADR signals are metastatic renal cell carcinoma, diffuse uveal melanocytic proliferation, renal cancer metastasis, connective tissue neoplasm and salivary gland fistula. Both drugs share significant ADRs including palmar-plantar erythrodysesthesia syndrome, disease progression and hyperkeratosis. Furthermore, subgroup analysis was conducted to explore sex difference in ripretinib and sunitinib.ConclusionThis study validated known AEs and identified new potential safety signals associated with ripretinib and sunitinib in GIST treatment. These findings contribute to the understanding of ripretinib and sunitinib, providing valuable evidence for improving its clinical use.